2017
DOI: 10.1021/acs.jpcc.7b04248
|View full text |Cite
|
Sign up to set email alerts
|

Normal and Inverted Hysteresis in Perovskite Solar Cells

Abstract: Hysteretic effects are investigated in perovskite solar cells in the standard FTO/TiO2/CH3NH3PbI3−xClx/spiro-OMeTAD/Au configuration.We report normal (NH) and inverted hysteresis (IH) in the J-V characteristics occurring for the same device structure, the behavior strictly depending on the pre-poling bias. NH typically appears at pre-poling biases larger than the open circuit bias, while pronounced IH occurs for negative bias pre-poling. The transition from NH to IH is marked by a intermediate mixed hysteresis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
117
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(130 citation statements)
references
References 38 publications
(113 reference statements)
7
117
0
1
Order By: Relevance
“…A different situation occurs when the initial polarization is negative, P 0 < 0, and an inverted hysteresis is evidenced, i.e. the current in forward scan is larger than in reverse [5]. Assuming the same parameters of the DEM and changing only P 0 = −P ∞ , we obtain the J-V characteristics depicted in Fig.…”
Section: Dynamic Hysteretic Effects -The τ Dependencementioning
confidence: 97%
See 3 more Smart Citations
“…A different situation occurs when the initial polarization is negative, P 0 < 0, and an inverted hysteresis is evidenced, i.e. the current in forward scan is larger than in reverse [5]. Assuming the same parameters of the DEM and changing only P 0 = −P ∞ , we obtain the J-V characteristics depicted in Fig.…”
Section: Dynamic Hysteretic Effects -The τ Dependencementioning
confidence: 97%
“…[5], i.e. the samples are pre-poled with an initial polarization P 0 and subsequently a reverse-forward (R-F) bias scan with constant rate α = ∂V/∂t is performed.…”
Section: Dynamic Hysteretic Effects -The τ Dependencementioning
confidence: 99%
See 2 more Smart Citations
“…In general, 'normal' hysteresis is the case where there occurs a large loss of photocurrent and fill factor (FF) during the reverse to forward voltage (R-F) scan, (also leading to a reduced open-circuit voltage, V OC ) as compared to the forward to reverse (F-R) scan. 14 Inverted hysteresis has been observed as a reduction in the short-circuit current (J SC ) for F-R scans compared to R-F scans by Shen et al 17 and Nemnes et al 18 while Tress et al 19 observed a loss in the FF in the form of an S-shaped kink for the F-R scan. Both normal and inverted hysteresis trends have been observed to become more acute for faster scans.…”
Section: Introductionmentioning
confidence: 95%